1999
DOI: 10.1002/(sici)1097-4644(19990315)72:4<570::aid-jcb12>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Plastic adherent stromal cells from the bone marrow of commonly used strains of inbred mice: Variations in yield, growth, and differentiation

Abstract: Bone marrow stroma contains a unique cell population, referred to as marrow stromal cells (MSCs), capable of differentiating along multiple mesenchymal cell lineages. A standard liquid culture system has been developed to isolate MSCs from whole marrow by their adherence to plastic wherein the cells grow as clonal populations derived from a single precursor termed the colony-forming-unit fibroblast (CFU-F). Using this liquid culture system, we demonstrate that the relative abundance of MSCs in the bone marrow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
292
1
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 481 publications
(315 citation statements)
references
References 31 publications
(26 reference statements)
14
292
1
1
Order By: Relevance
“…(17) ). However, it should be noted that BMSC cultures are heterogeneous and have been shown to include hematopoietic pre-B cells, granulocytic, and monocytic precursors, (18) as well as macrophages and endothelial cells. (19,20) It has been estimated that only 10% to 20% of the cells in a heterogeneous plasticadherent marrow cell culture are mesenchymal cells capable of differentiating into osteoblasts and adipocytes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(17) ). However, it should be noted that BMSC cultures are heterogeneous and have been shown to include hematopoietic pre-B cells, granulocytic, and monocytic precursors, (18) as well as macrophages and endothelial cells. (19,20) It has been estimated that only 10% to 20% of the cells in a heterogeneous plasticadherent marrow cell culture are mesenchymal cells capable of differentiating into osteoblasts and adipocytes.…”
Section: Introductionmentioning
confidence: 99%
“…(19,20) It has been estimated that only 10% to 20% of the cells in a heterogeneous plasticadherent marrow cell culture are mesenchymal cells capable of differentiating into osteoblasts and adipocytes. (18) Several methods now have been developed to purify populations of MSCs from mouse bone marrow. Stem cell antigen 1 (Sca-1), a marker previously described on hematopoietic stem cells, also has been described on mesenchymal osteoprogenitor cells and is directly required for their self-renewal.…”
Section: Introductionmentioning
confidence: 99%
“…Plastic-adherent cells from bone marrow are referred to as stromal cells (Friedenstein, 1976) and are thought to contain nonhematopoietic stem cells that can differentiate along multiple mesenchymal cell lineages (Prockop, 1997). The mononuclear cell fraction of bone marrow can be readily isolated by density gradient and contains stromal cells, hematopoietic and nonhematopoietic stem and precursor cells, and lymphocytes (Azizi et al, 1998;Phinney et al, 1999;Sasaki et al, 2001;Akiyama et al, 2002a). Transplantation of GFP-expressing mouse stromal cells by direct microinjection into the immunosuppressed rat indicates that these cells can form myelin in the demyelinated spinal cord (Akiyama et al, 2002b).…”
Section: Introductionmentioning
confidence: 99%
“…Attempts have been made to classify these subpopulations by marker expression and by shape and growth kinetics, e.g., as spindle-shaped type I or flattened type II cells (19) or as rapidly self-renewing cells, or mature MSC (15,16,20). In addition to the observed heterogeneity in vitro, variations have been observed in MSC cultures obtained from different species as well as from different rodent strains or individual human donors (21)(22)(23). Some studies (23) found that variations even exist among different MSC donations obtained from the same human donor.…”
mentioning
confidence: 99%